2022
DOI: 10.2807/1560-7917.es.2022.27.40.2200734
|View full text |Cite
|
Sign up to set email alerts
|

Very low risk of monkeypox among staff and students after exposure to a confirmed case in educational settings, England, May to July 2022

Abstract: We investigated a secondary school (11–16 year-olds), a primary school (5–11 year-olds), reception year (4–5 year-olds) and a nursery (2–5 year-olds) following confirmed monkeypox in an adult in each educational setting during June and July 2022. MVA-BN vaccine was offered up to 14 days post exposure to 186 children < 12 years and 21 were vaccinated. No secondary cases occurred among at least 340 exposed students and more than 100 exposed staff during the 28-day follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Most people are vulnerable to the current Mpox virus threat. Considering the escalating number of Mpox infection cases worldwide, the Advisory Committee on Immunization Practices (ACIP) recommends pre-exposure prophylaxis for health workers, laboratory personnel, clinical laboratory staff, and others who may be at risk of contracting Mpox [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most people are vulnerable to the current Mpox virus threat. Considering the escalating number of Mpox infection cases worldwide, the Advisory Committee on Immunization Practices (ACIP) recommends pre-exposure prophylaxis for health workers, laboratory personnel, clinical laboratory staff, and others who may be at risk of contracting Mpox [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review indicates a major gap in literature specifically, the research gap on school‐based interventions on mpox infection. Results from this scoping review did not reveal whether any intervention programs on mpox were introduced in the affected schools and whether such intervention had significant effects on low mpox transmission among young children 26 . While the authors reported low vaccine uptake, reasons for the low uptake were not reported and no study focused on this aspect of mpox control was identified in our review.…”
Section: Resultsmentioning
confidence: 77%
“…However, the epidemiology of mpox infection in England reflects a similar trend as almost all the cases occurred in adult population. Out of the 3390 infected persons, 99% and 1% were men and women, respectively.Whereas just one minor (0−15 years) was confirmed positive 26. Studies have linked human transmission of the mpox virus to prolonged exposure and close physical contact with positive cases.29 Whereas our review shows that the suspected cases only had fleeting contact with the positive cases in the four school settings, hence the low transmission risks.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…2 In England, outbreak investigations in educational settings, including a nursery where close contact between the case and the toddlers was unavoidable, found no secondary mpox cases among 340 children and 118 staff members exposed to a confirmed mpox case. 3 Similarly, despite 3582 cases confirmed in England between 6 May and 20 December 2022, including multiple household and other similar close-contact exposures to children, 4 only one case was confirmed in a child, a neonate with mpox and adenovirus co-infection. 5 Globally, reports of mpox disease in children and adolescents are also reassuring.…”
mentioning
confidence: 99%